2021
DOI: 10.1155/2021/9963450
|View full text |Cite
|
Sign up to set email alerts
|

The Stability Factors’ Sensitivity Analysis of Key Rock B and Its Engineering Application of Gob‐Side Entry Driving in Fully‐Mechanized Caving Faces

Abstract: To reveal the critical factors of the main roof influencing stability of surrounding rocks of roadways driven along goaf in fully-mechanized top-coal caving faces, this paper builds a structural mechanics model for the surrounding rocks based on geological conditions of the 8105 fully-mechanized caving face of Yanjiahe Coal Mine, and the stress and equilibrium conditions of the key rock block B are analyzed, and focus is on analyzing rules of the key rock block B influencing stability of roadways driven along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Sensitivity analysis serves as a fundamental instrument for importance ranking and the dimension reduction of input parameters [1], and its applications are spreading across diverse topics in civil engineering, such as strength analysis [2], failure analysis [3], rock mechanics [4], slope stability analysis [5], and structural reliability analysis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity analysis serves as a fundamental instrument for importance ranking and the dimension reduction of input parameters [1], and its applications are spreading across diverse topics in civil engineering, such as strength analysis [2], failure analysis [3], rock mechanics [4], slope stability analysis [5], and structural reliability analysis [6].…”
Section: Introductionmentioning
confidence: 99%
“…31 Wang et al established a mechanical model, combined with an orthogonal test and range method, analyzed the key factors affecting the stability of surrounding rock along gob excavation, and concluded that the key factors were essential top height and fracture location. 32 Zhang Baofeng et al studied the gob-side driving mechanism and surrounding rock control of a coal pillar with a 6 m considerable mining height and slight top unloading pressure by artificially controlling the basic top fracture location, optimizing top cutting Angle, top cutting depth, top cutting hole spacing and top cutting hole layout, etc. It was found that the combination of cutting-top pressure relief and supporting technology can ensure the stability of surrounding rock in the opening and stopping stages of small coal pillar excavation along the goaf.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great guiding significance for safe and efficient production of coal mine by analyzing the stress distribution and plastic characteristics of surrounding rock, and reasonably designing narrow coal pillar width and control technology. 6,7 In view of GED technology, scholars have mainly carried out the following research: (1) main advantages: in the low-stress zone, 8 improving the utilization rate of coal resources, 9,10 accelerating the excavating rate 11 ; (2) in terms of large deformation and failure mechanism of surrounding rock: a theoretical mechanical model of surrounding rock structure, 12,13 influence characteristics of basic roof thickness on surrounding rock stability, 14 disturbance mechanism of basic roof subsidence on narrow coal pillar, [15][16][17] failure mechanism of deep topcoal caving face, 18 distribution and evolution laws of surrounding rock displacement and stress 19,20 were studied; (3) narrow coal pillar width [21][22][23] and its control technology 24,25 were determined under specific conditions.…”
Section: Introductionmentioning
confidence: 99%